HUMAN PIG HEART TRANSPLANT: APPLICATION OF ABDULLAH SAEED'S CONTEXTUAL APPROACH TO QS. AL MAIDAH VERSE 3 - Nurmansyah, Ihsan; Oktaviana, Sherli Kurnia; Azid, Muhammad Adam Abd. (QiST: Journal of Quran and Tafseer Studies, 2023)
This paper discusses the contextualization of QS. al-Maidah: 3 regarding pig heart transplants in humans. This practice has become an interesting and viral issue on social media because a few months ago in the United States there was a medical finding about a pig heart transplant in humans which was successfully tested on the world's first patient. In responding to this there are differences of opinion, some allow and do not allow, of course it is very much influenced by the understanding of the text. Therefore, it is very important to review the interpretation of the text using Abdullah Saeed's contextual approach. The results of this study: 1) From a linguistic analysis point of view, the word khinzir means pig. Judging from the micro-macro asbab an-nuzul, pigs are not found in the midst of the Arab nation's historical life. 2) the interpretation of scholars from generation to generation towards the word lahmun khinzir has two main points. First, it is forbidden to eat pork. Second, the use of pig heart valves as a substitute for diseased human heart valves can be justified in an emergency. 3) contextualization. The use of pig heart in human heart transplantation is prohibited as long as there are other efforts that can be cured medically. However, if it is an emergency in order to protect one's life, then it is permissible on the condition that the recovery can only be done by means of a transplant and only done by a trusted specialist doctor.